Analysis of Vendor Selection Using Fuzzy Analytical Hierarchy Process (Fahp) (Case Study: Pt Pos Logistic Bandung) - Barus, Trisha Ranita; Widyawanto, Dimas; Triwijayanti, Lutfi; Rahmana, Arief; Yani, Santika (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to choose the best goods distribution vendor of PT Pos Logistic Bandung. Vendors are one of the main factors that influence the speed of delivery. Good decision making based on the results of vendor selection can improve performance in sales and operation management. Data were collected by conducting interviews and questionnaires to three expert in the sales and operations department. Data were analyzed using the Fuzzy Analytical Hierarchy method (FAHP) by converting the weight of the questionnaire to a triangular fuzzy number, calculating the fuzzy synthetic extent, vector, defuzzification ordinate, and normalizing the vector fuzzy value. Weights using the FAHP method will be compared with the results of the Expert Choice weights. The results of the study can be used by PT Pos Logistic sales and operation management in making decisions based on the conditions of the available vendors, the selected vendor is PT X with a weight of 0.300 (FAHP) and 0.452 (Expert Choice), both methods produce different weight values but the same selected vendor. This research can be developed specifically with the Topsis method by considering customer satisfaction. Based on previous research, several studies are used to weigh in choosing vendors, but not many have combined FAHP with Expert Choice.